Does MRI Breast "Density" (Degree of Background Enhancement) Correlate With Mammographic Breast Density?. Issue 2 (21st January 2014) - Hansen, Nienke L.; Kuhl, Christiane K.; Barabasch, Alexandra; Strobel, Kevin; Schrading, Simone
<x xml:space="preserve">Abstract</x> Purpose To investigate whether mammographic breast densities and the respective degree of MRI background enhancement would correlate. Mammographic breast density is coded to communicate how likely a cancer is obscured by parenchyma. Similarly, background enhancement in breast MRI could obscure enhancing cancer tissue. Materials and Methods A total of 468 women underwent standard full‐field digital mammography and dynamic contrast‐enhanced breast MRI in our institution. Mammographic breast density was scored according to the American College of Radiology‐classification; background enhancement in MRI was scored on a 4‐point scale from absent to severe. Breast "density classes" were retrospectively compared by analyzing the differences between scores for mammography and MRI. Statistical correlation was calculated using the Spearman coefficient. Results Scores matched in 19% of women (90/468) but differed in 81% (378/468). A deviation by 1 point was observed in 33% (157/468), by 2 points in 38% (179/468), by 3 in 9% (42/468). Scores for background enhancement were lower than mammographic scores in 371/468 (79.3%), equivalent in 90/468 (19.2%), and higher in 7/468 (1.5%). Conclusion Mammographic breast density does not correlate with the degree of background enhancement in MRI. In the majority of women, scores for background enhancement in MRI will be lower than the respective mammographic density scores. J. Magn. Reson. Imaging 2014;40:483–489. © 2014 Wiley Periodicals, Inc.